The basic features of ukrainian rural green tourism - Kulinchenko, K. O. (ТДАТУ, 2018)
The Ukrainian village has an extremely rich historical and architectural heritage, culture, and natural picturesque landscapes, as well as recreational resources. Besides, our villages are rich in individual housing stock and kind and hardworking people
Keywords: ukrainian rural green tourism; national importance; ukrainian traditions; socio-economic development